SOSIALISASI SEPAKTAKRAW KID’S DILINGKUNGAN DKI JAKARTA - Burhan Basyiruddin,; Achmad Sofyan Hanif; Abdul Gani; Jufrianis; Moh. Hanafi; abdian (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
AbstractThis Community Service aims to help sports staff in the DKI Jakarta environment to be able to understand the concept of Sepaktakraw Kid’s considering the current problems that many sepaktakraw athletes are injured at the age of students, this is due to the suitability of training and competition programs implemented by coaches, training programs athletes are forced to specialize at the age of elementary students, the number of events that are participated in the competition is the same as the number of events that are participated in elite athletes. The coaches want their athletes to get maximum performance faster and be able to win at a young age, so that athletes cannot reach the peak of achievement longer at their golden age. The implementation program will be carried out through seminars and workshops. First, the sports staff in the PSTI DKI Jakarta area will explain the stages in training for student athletes, especially the elementary and junior high levels. Furthermore, the participants can apply it in their respective schools/clubs. This community service is carried out in the DKI Jakarta area. This community service starts from May – October 2021. The result of this community service is that sepaktakraw coaches in the DKI Jakarta environment can understand the concept of sepaktakraw kid’s. AbstrakPengabdian Masyarakat ini bertujuan untuk membantu tenaga keolahragaan dilingkungan DKI Jakarta untuk dapat memahami konsep Sepaktakraw Kid’s mengingat permasalahan yang terjadi saat ini banyak atlet-atlet sepaktakraw yang mengalami cedera pada usia pelajar, ini disebabkan kesesuian program latihan dan kompetisi yang diterapkan oleh para pelatih, program latihan atlet dipaksa untuk melakukan spesialias di usia pelajar tingkat dasar, nomor event yang diikuti dalam pertandingan sama dengan nomor event yang diikuti pada elite athlete. Para pelatih menginginkan atlet nya lebih cepat mendapatkan prestasi maksimal dan dapat meraih juara di usia muda, sehingga para atlet tidak bisa mencapai puncak prestasi lebih lama pada usia emas nya. Program pelakasanaan akan dilakukan melalui seminar dan workshop, pertama para tenaga keolahragaan dilingkungan PSTI DKI Jakarta dijelaskan tahapan-tahapan dalam latihan bagi atlet pelajar khususnya tingkat dasar dan menengah pertama. Selanjutnya para peserta dapat mengaplikasikan nya dilingkungan sekolah/ klub masing masing. Pengabdian masyarakat ini dilaksanakan dilingkungan DKI Jakarta. Pengabdian masyarakat ini dimulai dari bulan Mei – Oktober 2021, Hasil pengabdian masyarakat ini adalah para pelatih sepaktakraw di lingkungan DKI Jakarta dapat memahami konsep sepaktakraw kid’s.